OsDDM1b Controls Grain Size by Influencing Cell Cycling and Regulating Homeostasis and Signaling of Brassinosteroid in Rice - Guo, Mingliang; Zhang, Wenchao; Mohammadi, Mohammad Aqa; He, Zhimei; She, Zeyuan; Yan, Maokai; Shi, Chao; Lin, Lingwei; Wang, Aqiong; Liu, Jindian; Tian, Dagang; Zhao, Heming; et al. (Frontiers in Plant Science, 2022)
Snf2 family proteins are an important chromatin-remodeling complex (CRC) subunit, contributing to the biological processes of transcription, replication, and DNA repair using ATP as energy. Some CRC subunits have been confirmed to be critical regulators in various aspects of plant growth and development and their role in epigenetic mechanisms, such as histone modification, DNA methylation and histone variants. However, the functions of Snf2 family genes in rice poorly investigated. In this study, the relative expression profile of 40 Snf2 family was studied at specific developmental stages of seed. Our results revealed that OsCHR741/OsDDM1b (Decrease in DNA methylation 1) was accumulated highly in the early developmental stage of seed. We further analyzed the OsDDM1b T-DNA insertion loss-function of mutant, which exhibits dwarfism, smaller organ size, and shorter, wider grain size and indifference in 1000-grain weight than the wild-type. Consistent with the grain size, the outer parenchyma cell layers of osddm1b lemma developed more cells with decreased size. OsDDM1b encoded a novel nucleus, membrane-localized protein and was distributed predominately in young spikelets and seeds, asserting its role in grain size. Meanwhile, the osddm1b was less sensitive to brassinosteroids (BRs) while the endogenous BR levels were increased. We detected changes in the expression levels of the BR signaling pathway and feedback-inhibited genes with or without exogenous BR application, and the alterations of expression also were observed in grain size-related genes in the osddm1b. Altogether, our results suggest that OsDDM1b plays a crucial role in grain size via cell proliferation, and regulates BR signaling and homeostasis.